Ganong's review of medical physiology - 4 0 16; Barrett, Kim E.;Ganong, William F.; 5 (Boston : McGraw-Hill Medical, 2010)
One of the world's leading texts on medical physiology, 'Ganong's Review of Medical Physiology' has been redesigned with a new full-colour format and expanded pedagogical features. Examples from clinical medicine are integrated the chapters to illustrate important physiologic concepts.
General principles & energy production in medical physiology -- Overview of cellular physiology in medical physiology -- Immunity, infection, & inflammation -- Excitable tissue: nerve -- Excitable tissue: muscle -- Synaptic & junctional transmission -- Neurotransmitters & neuromodulators-- Properties of sensory receptors -- Reflexes -- Pain & temperature -- Somatorsensory pathways -- Vision -- Hearing & equilibrium -- Smell & taste -- Electrical activity of the brain, sleep-wake states, & circadian rhythms -- Control of posture & movement -- The autonomic nervous system -- Hypothalamic regulation of hormonal functions-- Learning, memory, language, & speech -- The thyroid gland -- Endocrine functions of the pancreas & regulation of carbohydrate metabolism -- The adrenal medulla & adrenal cortex -- Hormonal control of calcium and phosphate metabolism & the physiology of bone-- The pituitary gland -- The gonads: development & function of the reproductive system -- Overview of gastrointestinal function & regulation-- Digestion, absorption & nutritional principles -- Gastrointestinal motilty -- Transport & metabolic functions of the liver -- Origin of the heartbeat & the electrical activity of the heart -- The heart as a pump -- Blood as a circulatory fluid & the dynamics of blood & lymph flow -- Cardiovascular regulatory mechanisms -- Circulation through special regions -- Pulmonary function -- Gas transport & pH in the lung-- Regualtion of respiration -- Renal function & micturition -- Regulation of extracellular fluid composition & volume -- Acidification of the urine & bicarbonate excretion.
A Lange medical book.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Physiology.;Physiology;Physiology. -- 20 -- Problems, exercises, etc; 20; 2